Influence of surface properties of the titanium dioxide porous films on the characteristics of solar cells - Serikov, T.M.; Ibrayev, N.Kh.; Nuraje, N.; Savilov, S.V.; Lunin, V.V. (Springer New York LLC, 2017)
Porous films formed by cylindrical geometrically anisotropic fragments of TiO2 have been produced by electrochemical anodization of titanium. The specific surface area and pore volume of the samples were determined by the BET method. It is shown that the samples have a bimodal pore-size distribution with maxima depending on the anodization voltage: by increase in voltage the inner diameter of the cylindrical pores grows, which leads to a decrease in the specific surface area. Dye sensitized solar cells were assembled on the basis of the obtained materials to study the effect of certain characteristics on the efficiency of solar energy conversion. The electrical transport properties of the films were studied by impedance spectroscopy. © 2017, Springer Science+Business Media, LLC.
Keywords: specific surface area; titanium dioxide nanotubes; efficiency of solar cells; electron transport properties